Features of determining the directions of building technological equipment development - RASHKIVSKYI, Volodymyr; IGNATENKO, Oleksandr (Ways to Improve Construction Efficiency, 2024)
The article describes the peculiarities of determining the directions of development of construction technological equipment used in the construction of frame buildings with prefabricated and monolithic frames. The results can be used in the organization of mechanized areas on construction sites during the reconstruction, restoration of buildings or during their new construction. The authors established the order of grouping the thematic areas of research, belonging to geographical zones and the dynamics of development from 2010 to 2024. The dynamics of patenting, searches for mechanized equipment, which is intended to accompany the technological processes of the construction of buildings with a prefabricated and monolithic frame, have been determined. This approach to research allows you to get a picture of the development of the subject based on generalized indicators and to narrow your search interests taking into account the specifics of the research, geographical interest, and the state of development of the research objects. In the publication, the authors present a research methodology for the development of structural and technological solutions for the mechanization of support for construction assembly processes. The relevance of the direction of development of mechanized technological modules, in particular, universal lifting modules, mobile technological modules for monolithic works is determined. Analytical studies of new structural and technological solutions for the mechanization of construction processes must be carried out in several stages: determination of thematic areas of research, specification of geographical time frames, determination of hidden implicit terms and requests describing the specifics of work performance, design features of technological equipment, their components, functional purpose, etc. The proposed methodology is based on the use of modern search databases, the use of artificial intelligence in the analysis and structuring of search results, and allows for the formation of approaches to the improvement of construction technologies for the construction of prefabricated and monolithic frame buildings. The defined approaches to the development of construction technological equipment allow making informed decisions to ensure the required technological level of mechanization of construction processes.